2020
DOI: 10.14309/ajg.0000000000001036
|View full text |Cite
|
Sign up to set email alerts
|

ACG Clinical Guideline: Management of Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome (IBS) is a highly prevalent, chronic disorder that significantly reduces patients' quality of life. Advances in diagnostic testing and in therapeutic options for patients with IBS led to the development of this first-ever American College of Gastroenterology clinical guideline for the management of IBS using Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) methodology. Twenty-five clinically important questions were assessed after a comprehensive literature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
696
2
34

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 499 publications
(736 citation statements)
references
References 246 publications
4
696
2
34
Order By: Relevance
“…Recent studies have showed that IBS patients have a worsening of symptoms after gluten/wheat ingestion so the consumption of these substances and gluten sensitivity have be considered involved in the etiology of IBS [ 103 , 104 , 105 , 106 ]; thus, a gluten-free diet is usually linked to a reduction of GI symptoms in IBS [ 92 ]. However, Guidelines 2020 recommended to verify if IBS-D patients are affected by celiac disease, performing the serological tests before giving a diet [ 9 ]. It is not clear if it is gluten that determines symptoms or other wheat components.…”
Section: Nutritional Protocols Used For Ibs-dmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have showed that IBS patients have a worsening of symptoms after gluten/wheat ingestion so the consumption of these substances and gluten sensitivity have be considered involved in the etiology of IBS [ 103 , 104 , 105 , 106 ]; thus, a gluten-free diet is usually linked to a reduction of GI symptoms in IBS [ 92 ]. However, Guidelines 2020 recommended to verify if IBS-D patients are affected by celiac disease, performing the serological tests before giving a diet [ 9 ]. It is not clear if it is gluten that determines symptoms or other wheat components.…”
Section: Nutritional Protocols Used For Ibs-dmentioning
confidence: 99%
“…Based on Roma IV criteria, IBS is classified according to the predominant stool pattern, recognized using the Bristol Stool Scale [ 2 ]. There are four different subtypes of IBS [ 8 , 9 ]: Constipation predominant IBS (IBS-C): more than 25% hard stools and less than 25% loose stools. Diarrhea predominant IBS (IBS-D): more than 25% loose stools and less than 25% hard stools.…”
Section: Introductionmentioning
confidence: 99%
“…The precise mechanisms by which these agents improve abdominal bloating in patients with IBS‐C are unclear but may relate to improvements in gastrointestinal transit and modulation of visceral sensation, which likely differs from patient to patient. Further studies to elucidate the pathophysiological processes involved are needed, as the results may translate into better treatments for this burdensome symptom of IBS‐C 75 …”
Section: Discussionmentioning
confidence: 99%
“… 3 Gut-directed hypnotherapy is recommended and is being increasingly applied to patients with IBS, which can achieve an effect similar to that of the low fermentable oligosaccharide, disaccharide, monosaccharide, and polyol diet; it can further be applied to inflammatory bowel disease to a lesser extent via its potential mechanism of action on the brain–gut axis. 16 – 18 Cognitive–behavioral therapy delivered by telephone or internet has also been shown superior to the usual treatment methods and is recommended for treating IBS. 19 , 20 Four classes of psychotherapy hold the most promise in CAPS: cognitive–behavioral therapy, psychodynamic interpersonal therapy, mindfulness/acceptance-based therapies and hypnotherapy, 1 although related clinical research is lacking.…”
Section: Discussionmentioning
confidence: 99%